2021
DOI: 10.2147/dmso.s304066
|View full text |Cite
|
Sign up to set email alerts
|

Understandings, Attitudes, and Barriers About Diabetes Care: Analysis of Factors Influencing Community Pharmacists in China

Abstract: Purpose Diabetes mellitus (DM) has been known as a major chronic health problem in China. Suboptimal management of diabetic patients may incur serious complications, even death. The quality of post-hospital care has a good relationship with community pharmacists. However, data describing the current situation from care between community pharmacists and patients in China are lacking. Our article is to investigate community pharmacists’ activities, evaluate their attitudes towards providing diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Most CPPs only provided basic traditional dispensing services like receipt of prescriptions, interpretation or evaluation of the prescriptions, and supply of the prescribed medication. The finding is consistent with earlier findings (Laliberté et al, 2012 ; Arif et al, 2023 ; Wang et al, 2021 ) that reported fewer participants actually involved in providing such activities. This may result from their limited knowledge and skills, which can result in their lower actual involvement in such healthcare services.…”
Section: Discussionsupporting
confidence: 93%
“…Most CPPs only provided basic traditional dispensing services like receipt of prescriptions, interpretation or evaluation of the prescriptions, and supply of the prescribed medication. The finding is consistent with earlier findings (Laliberté et al, 2012 ; Arif et al, 2023 ; Wang et al, 2021 ) that reported fewer participants actually involved in providing such activities. This may result from their limited knowledge and skills, which can result in their lower actual involvement in such healthcare services.…”
Section: Discussionsupporting
confidence: 93%
“…Although education levels are improving, the issue of an ageing population will remain a major challenge to the public health system in China [ 17 ]. A lack of knowledge about diabetes self-management has been reported as a major barrier in previous studies [ 18 20 ]. In our study, we found that patients’ knowledge about diabetes management was often missing (e.g., low awareness of diabetes complications), mistaken (e.g., intermitted medication use driven by the presence of symptoms), and easily misled (e.g., belief in health advice from quack doctors and false information in television advertisements).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature search was conducted before creating a self-administered questionnaire [ 21 , 23 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%